(untitled) (Journal of Fatima Jinnah Medical University, 2021)
Background: The liver is a major organ and involved in metabolizing various toxins, including chemicals, drugs, and natural substances.1 Diclofenac is a commonly used non-steroidal anti-inflammatory drug. Febuxostat is a novel non-purine xanthine oxidase inhibitor prescribed in various hyperuricemic states. Rise in liver enzymes with diclofenac use is a well-established fact. When both drugs are used in combination, these may lead to profound hepatotoxicity. To find out these facts this study was planned. Subjects and methods: An experimental study on mice was planned to explore these facts in University of Health sciences, Lahore. Animals were divided into 6 groups having 10 animals in each group. The animals were given drugs for 7 days. One served as control. 2nd group was given Diclofenac alone (100mg/kg), 3rd group was given Febuxostat (50mg/kg) alone while rest of three groups were administered drugs combination (Diclofenac + Febuxostat). Dose of Diclofenac (100mg/kg) kept constant while dose of Febuxostat increased in each group (5mg/kg, 10mg/kg and 50mg/kg). All drugs administered orally by gavage. After 7 days, the serum levels of liver enzymes assessed. Statistical analysis was performed using SPSS 20. One way ANOVA and Post hoc Tukey tests were applied. A p-value of ≤0.05 was considered statistically significant. Results: The results showed that Diclofenac and Febuxostat caused liver damage when used separately but hepatotoxicity was much significant (p-value <0.001) when drugs were used in combination. Conclusion: Both drugs Diclofenac and Febuxostat when administered in combination, causes more liver profound liver damage. That is why their use in combination should be avoided in clinical settings.